Weekly patterns and sociodemographic correlates of adults’ objectively measured physical activity and sedentary behavior - Sayaka Kurosawa; Kaori Ishii; Ai Shibata; Mohammad Javad Koohsari; Koichiro Oka (PLoS ONE, 2025)
Objectives As well as the dose-response association of physical activity (PA), its combination with other behaviors and daily patterns are associated with health outcomes. Identifying the prevalence of objectively assessed weekly patterns of PA and sedentary behavior (SB) and sociodemographic correlates may contribute to maximizing beneficial intervention strategies. Methods We assessed PA and SB using an accelerometer among 684 participants aged 40–64 years from two Japanese localities. PA and SB combinations were defined as ‘Couch potato’ (low PA and high SB), ‘Light mover’ (low PA and low SB), ‘Sedentary exerciser’ (high PA and high SB), and ‘Busy bee’ (high PA and low SB). Weekly PA patterns were defined as ‘Inactive’ (low PA), ‘Weekend warrior’ (high PA and PA mainly on the weekend), and ‘Regularly active’ (high PA and PA throughout the week). To identify differences in characteristics across the groups, analysis of variance with post-hoc Bonferroni multiple comparison tests was used for continuous variables. For categorical variables, group differences were examined using χ2 tests with post-hoc residual analyses. Results Regarding PA and SB combinations, ‘Couch potato’ and ‘Busy bee’ groups were approximately one-third each, and ‘Light mover’ and ‘Sedentary exerciser’ were approximately one-fifth-to-sixth. Regarding weekly PA patterns, 16.6% and 38.9% of the participants were categorized as ‘Weekend warrior’ and ‘Regularly active’, respectively. Almost 45% of participants were categorized as ‘Inactive’. The characteristics were defined for each category. For instance, women and participants with lower educational attainment were more likely to be ‘Light mover’. Participants with higher educational attainment were more likely to be ‘Weekend warrior’, whereas age and sex were not significantly associated with weekly PA patterns. Conclusions Initiatives to address PA and SB could focus on total amounts and appropriate combinations and patterns depending on the characteristics of the target subgroup.